Efficacy of empagliflozin in heart failure with preserved versus mid-range ejection fraction: a pre-specified analysis of EMPEROR-Preserved - Anker, Stefan; Butler, Javed; Usman, Muhammad Shariq; Filippatos, Gerasimos; Ferreira, João Pedro; Bocchi, Edimar; Böhm, Michael; Rocca, Hans Pieter Brunner-La; Choi, Dong-Ju; Chopra, Vijay; Chuquiure, Eduardo; Giannetti, Nadia; et al. (Nature medicine, 2022)
The EMPEROR-Preserved trial showed that the sodium-glucose co-transporter 2 inhibitor empagliflozin significantly reduces the risk of cardiovascular death or hospitalization for heart failure (HHF) in heart failure patients with left ventricular ejection fraction (LVEF)  > 40%. Here, we report the results of a pre-specified analysis that separately evaluates these patients stratified by LVEF: preserved (≥ 50%) (n = 4,005; 66.9%) or mid-range (41-49%). In patients with LVEF  ≥ 50%, empagliflozin reduced the risk of cardiovascular death or HHF (the primary endpoint) by 17% versus placebo (hazard ratio (HR) 0.83; 95% confidence interval (CI): 0.71-0.98, P = 0.024). For the key secondary endpoint, the HR for total HHF was 0.83 (95%CI: 0.66-1.04, P = 0.11). For patients with an LVEF of 41-49%, the HR for empagliflozin versus placebo was 0.71 (95%CI: 0.57-0.88, P = 0.002) for the primary outcome (Pinteraction = 0.27), and 0.57 (95%CI: 0.42-0.79, P < 0.001) for total HHF (Pinteraction = 0.06). These results, together with those from the EMPEROR-Reduced trial in patients with LVEF < 40%, support the use of empagliflozin across the full spectrum of LVEF in heart failure.